Terapia ocupacional e surdocegueira: uma revisão de escopo - Gracia, Rayra Soares (Universidade Federal de São Carlos, 2023)
Deafblindness is the loss of sight and hearing simultaneously. historically the Occupational Therapy has turned to the assistance of people with a disability. A This research aimed to investigate the production of knowledge both in Therapy Occupational and other areas of knowledge, in the national and international literature on the topic of deafblindness. This is a scope review carried out in journals specific areas of Occupational Therapy in Brazil, namely Cadernos Brasileiros de Occupational Therapy at UFSCar (CaBTO), Journal of Occupational Therapy at USP (Magazine TO-USP), Revista Baiana de Terapia Ocupacional and Revista Interinstitucional Brasileira de Occupational Therapy (RevisBrato) and in the bases Scielo.br, Portal de Periódicos CAPES and Academic Google. For inclusion and composition of the sample, publications were considered available online, regardless of study objectives, population or methodology, published from 1990 to 2022. The sample consisted of 36 publications, none of which of them appeared in specific national journals in the field of Occupational Therapy, but Four publications were found in the international literature on deafblindness in occupational therapist authors. In relation to the other areas, Education was identified Special (n=16), Pedagogy (n=5), Medicine (n=5), Psychology (n=3), Arts (n=2), Speech Therapy (n=2), Mathematics (n=1), Dentistry (n=1), History (n=1), System of Information (n=1), Optometry (n=1). focus on the participation of people with DEAFBLINDNESS. The focus of publications in the area of ​​Occupational Therapy was on the participation of people with deafblindness in occupations, in the context in which these people are inserted and in the role of the occupational therapist as a professional who identifies factors that support or inhibit occupational performance and that acts under the premise of occupational justice to guarantee the rights of these people. Regarding the focus of publications in the areas identified, the communication and education of the deafblind person was evidenced. Concludes that there is an incipient production of knowledge about this population, being necessary to future research to discover and fill knowledge gaps about the theme.
Occupational therapy and deafblindness: a scoping review
Keywords: Surdocegueira; Terapia Ocupacional; Revisão de literatura; Deafblindness; Occupational therapy; Literature review; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL